2010
DOI: 10.1007/s12576-010-0106-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between plasma and saliva adrenocortical hormones in response to submaximal exercise

Abstract: This study examined the relationships between plasma and saliva adrenocortical hormones in response to long-duration submaximal exercise. In nine healthy, physically active, female volunteers, blood and saliva samples were taken at rest and every 30 min during a 120-min cycling trial at 50-55% VO(2max) for cortisol and dehydroepiandrosterone (DHEA) analysis. Correlation analysis revealed a moderate but significant relationship between plasma and saliva cortisol (r = 0.35, P < 0.02) and plasma and saliva DHEA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Broad range correlations (r = 0.35 to r = 92) between salivary and plasma/serum cortisol during and following exercise have been reported [5,7,11,17,22]. Our correlations between plasma and salivary cortisol induced by exercise were significant in the PM (r = 0.81) and the AM (r = 0.61), but the difference did not reached significance (p = 0.10).…”
Section: Discussioncontrasting
confidence: 43%
“…Broad range correlations (r = 0.35 to r = 92) between salivary and plasma/serum cortisol during and following exercise have been reported [5,7,11,17,22]. Our correlations between plasma and salivary cortisol induced by exercise were significant in the PM (r = 0.81) and the AM (r = 0.61), but the difference did not reached significance (p = 0.10).…”
Section: Discussioncontrasting
confidence: 43%
“…Lipid-soluble steroids travel by passive diffusion, passing through the capillary wall, basement membrane, and acinar cells of the secretory endpieces along a concentration gradient [33]. Thus, saliva concentrations of unconjugated steroids reflect the unbound plasma concentration [6,12,39,42], on condition that the appropriate methods are used [20,27]. Steroids are usually very slightly metabolized in saliva.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, the effects on body composition and metabolic responses were estimated. Noninvasive saliva samples were taken for rest and end-exercise DHEA, testosterone and cortisol measurements, despite some reservations regarding saliva testosterone [16,20,26,27], as this was a field study and the blood/saliva correlation for steroid hormone concentrations has been found to be high [6,12,39,42]. We hypothesized that DHEA administration would result in improved performance in these young female athletes and significant changes in their body composition and saliva steroid hormone concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these hormones have been used as stress markers [11,25,33]. Bernstein et al [34] investigated an association between sympathetic responsiveness and the serum concentration of IL-6 in young women.…”
Section: Exercise Effectsmentioning
confidence: 99%
“…Recently, saliva sampling has received attention as an alternative to blood sampling to measure stress markers [8][9][10][11]. Saliva collection has the advantage over blood sampling in that it is a non-invasive method of sample collection which does not require any specialized training.…”
Section: Introductionmentioning
confidence: 99%